2010
DOI: 10.1111/j.1462-2920.2009.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifreeze proteins in polar sea ice diatoms: diversity and gene expression in the genus Fragilariopsis

Abstract: Fragilariopsis is a dominating psychrophilic diatom genus in polar sea ice. The two species Fragilariopsis cylindrus and Fragilariopsis curta are able to grow and divide below freezing temperature of sea water and above average sea water salinity. Here we show that antifreeze proteins (AFPs), involved in cold adaptation in several psychrophilic organisms, are widespread in the two polar species. The presence of AFP genes (afps) as a multigene family indicated the importance of this group of genes for the genus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 46 publications
7
92
0
Order By: Relevance
“…That said, the highest isoprene producer in this study, P. capsulatus CCMP, is also a member of the Chlorophyta, and similarly Shaw et al (2003) showed that the chlorophyte Micromonas putida CCMP 489 produced relatively high concentrations of isoprene. This suggests that the similarly low production rates measured here and elsewhere for D. tertiolecta (Bonsang et al 2010) appear to be species-specific, rather than a broader taxonomic phenomenon among chlorophytes, which is further supported by the relatively high isoprene production demonstrated by the macroalga Ulva intestinalis (Broadgate et al 2004). Clearly, given the ecological and biogeochemical importance of chlorophytes in aquatic environments, the nature and extent of variability within this class requires further attention.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…That said, the highest isoprene producer in this study, P. capsulatus CCMP, is also a member of the Chlorophyta, and similarly Shaw et al (2003) showed that the chlorophyte Micromonas putida CCMP 489 produced relatively high concentrations of isoprene. This suggests that the similarly low production rates measured here and elsewhere for D. tertiolecta (Bonsang et al 2010) appear to be species-specific, rather than a broader taxonomic phenomenon among chlorophytes, which is further supported by the relatively high isoprene production demonstrated by the macroalga Ulva intestinalis (Broadgate et al 2004). Clearly, given the ecological and biogeochemical importance of chlorophytes in aquatic environments, the nature and extent of variability within this class requires further attention.…”
Section: Discussionmentioning
confidence: 60%
“…Data shown are the means for all strains analyzed in triplicate during this study (white bars) from each taxonomic group 6 standard error (SE) normalized to Chl a. Results from previous research are shown in gray bars for comparison (Shaw et al 2003;Gantt et al 2009;Bonsang et al 2010). The numbers of samples are included above each data point, and refer to the number of strains analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations